Tarnished gold—the “standard” urine culture: reassessing the characteristics of a criterion standard for detecting urinary microbes - Brubaker, Linda; Chai, Toby C.; Horsley, Harry; Khasriya, Rajvinder; Moreland, Robert B.; Wolfe, Alan J. (Frontiers in Urology, 2023)
Diagnosis and treatment of urinary tract infection (UTI) remains stagnant. The presumption that a patient either has a UTI or not (binary choice) is inappropriately simplistic. Laboratory diagnostic tests have not advanced for decades. The goal of UTI treatment has not been rigorously defined and may increase prescription of potentially harmful, inappropriate antibiotics. Despite the high incidence of UTI diagnosis, the high cost of UTI treatment, and increasing concerns associated with antimicrobial resistance, the development of novel and more accurate UTI tests have not been considered as priorities, in part, due to the general perception that current UTI care is already sufficient. In this This is a provisional file, not the final typeset article review, we discuss the importance of improving UTI diagnostic testing to improve treatment outcomes. We discuss the problems associated with UTI diagnosis. Urinary microbes are alive and exist in both healthy and symptomatic individuals -urine is not sterile. We specifically outline the limitations of standard urine culture methods used by clinical microbiology laboratories, explaining clearly why such methods cannot be considered to be the "gold standard," as standard culture underreports most of the urinary tract microbes, including some acknowledged and many emerging uropathogens. We do not recommend abandonment of this test, as no universally accepted substitute yet exists. However, we strongly encourage the development of new and improved diagnostic tests that can both improve outcomes and preserve antibiotic stewardship.